Intertemporal Wage Variation, Employment, and Unemployment - Adams, James D. (Journal of Labor Economics, 1987)
A model of labor supply under uncertainty is developed, and comparative statics of current labor are carried out with respect to temporary and persistent wage change. This and a complementary analysis of measurement error suggest that individual wage growth leads to downward-biased estimates of intertemporal labor substitution. An alternative strategy, namely, the use of short-lived industry wage pulses in place of individual wage growth, is free of the above biases. Findings presented in the paper support this point of view. These results also suggest that intertemporal substitution has been undervalued as a source of cyclical changes in unemployment.